A Framework for Executing Protein Sequence Alignment in Cloud Computing Services - Carvalho, Leonardo Reboucas de; Melo, Alba Cristina Alves; Araujo, Aleteia (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2021)
Protein sequence alignment is a task of great relevance in Bioinformatics and the Hirschberg algorithm is widely used for this task. This work proposes a framework for executing sequence alignment with the Hirschberg algorithm in different cloud computing services. In experiments, our framework was used to align HIV-1 protease sequences using different instances of AWS EC2 and different configurations of AWS Lambda functions.The results show that, for this application, there is a tradeoff between the expected execution time and the cost, e.g., in most cases AWS Lambda provides the best runtime, however at a higher USD cost. In this context, it is important to have a framework that helps in deciding which approach is most appropriate.